A lifetime of changing calls: North Atlantic right whales, Eubalaena glacialis, refine call production as they age. (March 2018) - Root-Gutteridge, Holly; Cusano, Dana A.; Shiu, Yu; Nowacek, Douglas P.; Van Parijs, Sofie M.; Parks, Susan E.
Abstract : The trajectory of development and refinement of communication signals closely map physical and social development in many vertebrate species. Although marine mammals exhibit highly complex and diverse communication signals, asking similar questions about signal development can be challenging when dealing with long-lived species that roam widely at sea. North Atlantic right whales, a large baleen whale species, are intensely studied due to their endangered status. We examine whether right whale acoustic signals vary with the physical and social development of individuals from birth to adulthood using a latitudinal analysis. Data included 986 high-quality calls recorded from 49 individuals of known age spanning from 1 month to 37 years, with two individuals measured at different ages. Calls produced by calves younger than 1 year were easily distinguished by their short duration, a high degree of frequency modulation and a high percentage of nonlinear phenomena. Nonlinear phenomena within calls shifted from disorder (deterministic chaos) to increased control (biphonation and subharmonics) with increasing age. The overall percentage of calls containing nonlinear phenomena decreased with increasing age. Duration of the calls and calling bouts increased in direct correlation with age. Notably there was no clear indication of fixation in any of the measured parameters with age, with directional changes continuing over the entire age range studied. This study presents the first evidence that acoustic maturation does not stop at sexual maturity (∼9 years) in right whales and that refinement of calls continues through adulthood. Clear age-related voice cues have been documented in a range of terrestrial species with increases in call duration often reflecting increased stamina or condition in older adults. This study shows a similar trend in right whale sound production, with changes detectable across three-decade age range of available data. Highlights: North Atlantic right whale calls continually change with increasing age. Calls continued to increase in duration with age past maturity. Nonlinear chaos continued to change with age past maturity as seen in humans. Physical maturity did not result in crystallization or stabilization of repertoire. Changes appeared to be lifelong.